Російський досвід випуску іпотечних облігацій та перспективи його застосування в Україні - Зельцер, Є. Р. (Ways to Improve Construction Efficiency, 2012)
The four issues of mortgage bonds organized by Russian Open joint-stock company «The Agency for Housing Mortgage Lending» were analyzed in the article. The possibilities to use the Russian experience in Ukraine have been studied.